Engineering and in vitro evaluation of acid labile cholesterol tethered MG132 nanoparticle fortargeting ubiquitin-proteasome system in cancer - Ghosh, Chandramouli; Gupta, Neha; More, Piyush; Sengupta, Poulomi; Mallick, Abhik; Santra, Manas Kumar; Basu, Sudipta (Chemistryselect, 2016)
In recent years, proteasome has evolved as one of the important alternative targets in cancer chemotherapy. However, selective targeting of proteasome system in cancer cells still remains a major challenge. To address this, a potent peptide based proteasome inhibitor MG132 was chemically conjugated with biocompatible-biodegradable cholesterol by acid cleavable hydrazone linkage. Spherical nanoparticles (MG132-NPs) were engineered from cholesterol-MG132 conjugate. Increased amount of free MG132 was released from these nanoparticles in acidic environment compared to physiological milieu in a slow and controlled manner. These MG132-NPs were taken up by breast cancer MCF7 cells into lysosomes within 6 h. Proteasome system was inhibited by these MG132-NPs leading to stabilization of beta-catenin, cyclin A and cyclin B in HEK-293T cells. Interestingly, MG132-NPs induced much improved cell death in drug resistant MDA-MB-231 cells with insignificant toxicity in healthy cells (HEK293 and L929) even in higher concentration.

Cisplatin-induced self-assembly of graphene oxide sheets into spherical nanoparticles for damaging sub-cellular DNA - Nandi, Aditi; Mallick, Abhik; More, Piyush; Sengupta, Poulomi; Ballav, Nirmalya; Basu, Sudipta (Chemical Communications, 2017)
This report describes the hitherto unobserved cisplatin induced self-assembly of 2D-graphene oxide sheets into 3D-spherical nano-scale particles. These nanoparticles can encompass dual DNA damaging drugs simultaneously. A combination of confocal microscopy, gel electrophoresis and flow cytometry studies clearly demonstrated that these novel nanoparticles can internalize into cancer cells by endocytosis, localize into lysosomes, and damage DNA, leading to apoptosis. Cell viability assays indicated that these nanoparticles were more cytotoxic towards cancer cells compared to healthy cells.